Magnetohydrodynamic flow and Hall current effects on a boundary layer flow and heat transfer over a three-dimensional stretching surface. Issue 1 (31st December 2023) - Ferdows, M.; Ramesh, G. K.; Madhukesh, J. K.
Abstract : The current investigation is being carried out to investigate the impacts of magnetohydrodynamic flow and hall current effects on boundary layer flow across a three-dimensional stretching surface. The governing equations are framed with reasonable assumptions, and appropriate similarity transformations are applied to convert a set of partial differential equations into ordinary differential equations. To solve the reduced equations, the Runge Kutta Fehlberg 4th 5th order technique is utilised. The results reveal that primary and secondary velocity improves with the velocity parameter and Eckert number decrease for the magnetic parameter. The improvement in the Grashof number will improve the primary velocity but a reverse trend is seen in the case of secondary velocity. The thermal profile improves with the magnetic parameter, the velocity parameter, and the Eckert number, but it degrades with the Grashof number. The rate of heat transmission increases with the magnetic parameter and the Eckert number, whereas it decreases with the remaining factors.